Identifikasi Preferensi UKM Dalam Mencari Sumber Pembiayaan Dari Lembaga Keuangan Mikro di Wilayah Kota Yogyakarta - Sri Utami; Cintya Hartanti Hutaminingrum; Hery Purnomo (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2022)
SMEs are one of the components driving economic growth which is supported by the existence of Microfinance Institutions. This study aims to look at the pattern of preferences and the factors that influence the preferences of SMEs in finding sources of financing for Microfinance Institutions. Cluster random sampling was used by distributing questionnaires and structured interviews with samples of MSMEs in Yogyakarta City, especially Umbulharjo District and Kotagede District. Meanwhile, a questionnaire was also given to MFIs to see their perceptions of SMEs. The data is processed using descriptive statistics and will be interpreted quantitatively and qualitatively. From the results of the analysis of respondents' preferences in general, some factors determine the selection of MFIs by customers in each MFI forming the segmentation. The conclusion is that banking MFIs are distinguished from non-banking MFIs. The determining factor for banking MFIs is the selection of MFIs by customers to serve both administrative speed and MFIs that are easily accessible from the location. The average determinant of non-bank MFIs in selecting good services is administrative speed and proximity to public transportation. The average segmentation preferences of SMEs for each MFI are: for respondents, banking MFIs are used to dealing with banks and are more oriented toward business development, looking for non-banking MFIs in the southwest, choosing MFIs because they are related to cooperatives, respondents have a high level of religion. relatively strong, simple administration with a fast time and there is an emotional connection between customers with cooperatives and BMT. This shows that cooperatives are trying to get customers from micro, business and individual income are each below IDR 5 million, stating the case that BMT is trying to get customers from micro, but business and individual incomes are smaller than customers in the cooperative segment which is below IDR 1 million. Keywords: Preference, UMKM, LKM Abstrak UKM merupakan salah satu komponen penggerak pertumbuhan ekonomi yang didukung oleh keberadaan Lembaga Keuangan Mikro. Penelitian ini bertujuan melihat pola preferensi dan faktor-faktor yang mempengaruhi preferensi UKM dalam mencari sumber pembiayaan Lembaga Keuangan Mikro. Melalui penyebaran kuesioner dan wawancara terstruktur dengan sampel UMKM yang terpilih melalui cluster random sampling di Kota Yogyakarta khususnya Kecamatan Umbulharjo dan Kecamatan Kotagede. Sementara itu, kuesioner juga diberikan kepada LKM untuk melihat persepsi mereka terhadap UKM. Data diolah dengan menggunakan statistik deskriptif dan akan diinterpretasikan secara kuantitatif dan kualitatif. Hasil analisis preferensi responden secara umum, terdapat faktor penentu pemilihan LKM oleh nasabah pada setiap LKM pembentuk segmentasi. Kesimpulan bahwa LKM perbankan dibedakan dengan LKM non perbankan. Faktor penentu LKM perbankan dipilih oleh nasabah karena kecepatan administrasi pelayanan dan LKM yang mudah dijangkau dari lokasi. Rata-rata faktor penentu LKM non bank dipilih adalah karena pelayanan yang baik dengan kecepatan administrasi dan dekat dengan angkutan umum. Preferensi segmentasi rata-rata UKM untuk masing-masing LKM adalah: LKM perbankan sudah terbiasa berurusan dengan bank dan lebih berorientasi pada pengembangan usaha sedangkan LKM non perbankan karena berkaitan dengan koperasi, responden memiliki tingkat religi yang relatif kuat, administrasi yang sederhana dengan waktu yang cepat serta adanya hubungan emosional antara nasabah dengan koperasi dan BMT. Hal ini menunjukkan bahwa koperasi berusaha mendapatkan nasabah dari mikro, pendapatan usaha dan individu masing-masing di bawah Rp5 juta. BMT berusaha mendapatkan pelanggan dari mikro, tetapi pendapatan usaha dan individu lebih kecil dari pelanggan segmen Koperasi yang dibawah Rp1 juta Kata kunci: Preference, UMKM, LKM